LEX CRYPTO: PERBANDINGAN LANDASAN HUKUM TERHADAP DAMPAK KEBERADAAN BITCOIN ANTARA INDONESIA DENGAN EL SALVADOR - Aditya Rafi Fauzan; Rianda Dirkareshza (Fakultas Hukum Universitas Negeri Semarang, 2021)
The Indonesian state certainly does not want its currency to be replaced by a digital system that has a fairly high fluctuating value. Unlike the case with the Republic of El Salvador, which actually welcomes the presence of bitcoin in its country by making it a legal tender. This study aims to compare the legal basis between Indonesia and El Salvador on the impact of the existence of bitcoin in order to analyze the reasons why Indonesia classifies bitcoin as a commodity and not as an electronic payment system by comparing it to El Salvador which legalized bitcoin as a currency, as well as knowing the importance of developing the foundation law against bitcoin so that it can have a positive impact on the economy. The research method used in this study uses a comparative approach. The results of this study indicate that buying and selling bitcoin as an intangible and valuable object becomes an alternative investment for the Indonesian people and is not allowed to be used as a legal tender. The development of regulations related to taxes, security and ease of doing business is also a positive impact that can be taken from the existence of crypto assets in Indonesia. El Salvador uses bitcoin as a digital payment system aimed at creating financial inclusion for its people, while Indonesia already has its own financial inclusion in rupiah. This study recommends the need for caution in the application of the next legal basis for crypto assets in Indonesia because it can eliminate the positive impact on the economy